2017
DOI: 10.3889/oamjms.2017.050
|View full text |Cite
|
Sign up to set email alerts
|

Association among Thyroid Dysfunction, Asthma, Allergic Rhinitis and Eczema in Children with Alopecia Areata

Abstract: BACKGROUND:Alopecia areata is a non-scarring hair loss, which typically starts quickly. Atopy is one of the possible predisposing risk factors for this condition.AIM:This study aimed to evaluate the prevalence of thyroid disease, atopic dermatitis and allergic diseases in children with alopecia areata and compare the results with healthy individuals.METHODS:This case-control study was conducted on 50 patients with alopecia areata, diagnosed by a dermatologist, and 150 healthy individuals as the control group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…The prevalence of asthma in hair loss patients ranged from 9.9 to 10.3%, compared to 6.5–7.7% for controls ( p ≤ 0.001–0.064) [27, 28]. No statistical association was identified in 4 other case-control studies (4,918 AA patients and 784,330 control patients) [21, 28-30]. The nationwide study of Chu et al [21] derived from the Taiwanese National Insurance Registry identified a statistically significant association between AA and several autoimmune diseases including AD, AR, psoriasis, thyroid disease, vitiligo, SLE, and diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of asthma in hair loss patients ranged from 9.9 to 10.3%, compared to 6.5–7.7% for controls ( p ≤ 0.001–0.064) [27, 28]. No statistical association was identified in 4 other case-control studies (4,918 AA patients and 784,330 control patients) [21, 28-30]. The nationwide study of Chu et al [21] derived from the Taiwanese National Insurance Registry identified a statistically significant association between AA and several autoimmune diseases including AD, AR, psoriasis, thyroid disease, vitiligo, SLE, and diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
“…A significant association was found between family history of atopy and allergic disorders and AA, with 28% of AA patients reporting a positive family history compared to 4% of controls ( p = 0.046) [21, 27-30]. Three cross-sectional studies regarding asthma and hair loss with a total 1,600 patients reported the prevalence of asthma among AA patients of 1.34–14.5%; however there was no reported association with early onset of AA or development of alopecia totalis or universalis [20, 31, 32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study had a retrospective cohort design, one study was cross‐sectional and the other 15 were case–control studies . Two studies exclusively examined adults (aged ≥18 years), one study examined children (aged <18 years) and another 14 studies included both age groups . A summary of the included studies is shown in Table .…”
Section: Resultsmentioning
confidence: 99%